NORMAL FASTING BLOOD SUGAR LEVELS AND MEDICATION ADHERENCE IMPROVE THE QUALITY OF LIFE OF TYPE 2 DIABETES MELLITUS PATIENTS IN PRIMARY HEALTH FACILITIES - Hidayati, Titiek; Fatimah, Siti Nur; Iskandar, Shelly (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of the overall study was to determine the quality of life (QOL) and the factors that influence it in patients with diabetes mellitus (DM) in primary health care (PHC) Jetis 1, Bantul. Methods: This cross-sectional study was conducted on 153 DM patients in PHC Jetis I, Bantul. Respondents were recruited by inclusion and exclusion criteria. Primary data on exposure to cigarette smoke, adherence with physical activity, perception of disease, and QOL are collected through interviews. Data were analyzed by a mean test for ratio scale data and Chi-square test. Results: The results showed that the QOL and the level of adherence of DM patients in Puskesmas Jetis I were classified as very good. Male patients, elementary school graduates, normal body mass index (BMI), normal fasting blood sugar levels, adherent DM medication, and positive disease perception have a greater chance of having a better QOL. The mean of the random blood sugar and the fasting blood sugar levels exceeded the normal values, with 261.70 Â± 121.15 mg/dl and 167.43 Â± 10.23, respectively. Conclusion: The QOL of DM patients in I Jetis PHC is very good. Men, normal BMI, adherent with medication therapy, and normal fasting sugar levels are associated with an increase in QOL.